Well-Defined Rhodium–Gallium Catalytic Sites in a Metal–Organic Framework: Promoter-Controlled Selectivity in Alkyne Semihydrogenation to E‑Alkenes - Desai, Sai Puneet; Ye, Jingyun; Zheng, Jian; Ferrandon, Magali S; Webber, Thomas E; Platero-Prats, Ana E; Duan, Jiaxin; Garcia-Holley, Paula; Camaioni, Donald M; Chapman, Karena W; Delferro, Massimiliano; Farha, Omar K; et al. (Journal of the American Chemical Society, 2018)
Promoters are ubiquitous in industrial heterogeneous catalysts. The wider roles of promoters in accelerating catalysis and/or controlling selectivity are, however, not well understood. A model system has been developed where a heterobimetallic active site comprising an active metal (Rh) and a promoter ion (Ga) is preassembled and delivered onto a metal–organic framework (MOF) support, NU-1000. The Rh–Ga sites in NU-1000 selectively catalyze the hydrogenation of acyclic alkynes to E-alkenes. The overall stereoselectivity is complementary to the well-known Lindlar’s catalyst, which generates Z-alkenes. The role of the Ga in promoting this unusual selectivity is evidenced by the lack of semihydrogenation selectivity when Ga is absent and only Rh is present in the active site.